Targeting Ferroptosis with Small Molecule Atranorin (ATR) as a Novel Therapeutic Strategy and Providing New Insight into the Treatment of Breast Cancer - Mine Ensoy; Demet Cansaran-Duman (MDPI AG, 2024)
Background/Objectives: Ferroptosis results from the accumulation of iron-dependent lipid peroxides and reactive oxygen species (ROS). Previous research has determined the effect of atranorin (ATR) on other cell death mechanisms, but its potential for a ferroptotic effect depending on ROS levels is unclear. This study details the therapeutic role of small-molecule ATR through ferroptosis by suppressing MDA-MB-231, MCF-7, BT-474, and SK-BR-3 breast cancer cells. Methods: The anti-proliferative effect of ATR on cells was evaluated by xCELLigence analysis, and ferroptotic activity was evaluated by enzymatic assay kits. The changes in gene and protein expression levels of ATR were investigated by the qRT-PCR and western blot. In addition, mitochondrial changes were examined by transmission electron microscopy. Results: ATR was found to reduce cell viability in cancer cells in a dose- and time-dependent manner without showing cytotoxic effects on normal breast cells. In BT-474 and MDA-MB-231 cells, ATR, which had a higher anti-proliferative effect, increased iron, lipid peroxidation, and ROS levels in cells and decreased the T-GSH/GSSG ratio. The results revealed for the first time that small-molecule ATR exhibited anti-cancer activity by inducing the glutathione pathway and ferroptosis. Conclusions: This study highlights the potential of ATR as a drug candidate molecule that can be used in the development of new therapeutic strategies for the treatment of triple-negative and luminal-B breast cancer subtypes.